The Impact of Integrated, Listening, Hand, Attention, Matching (ILHAM) technique on Madrasah Aliyah students' Self-Control - Sulaeman; Herdianto Wahyu Pratomo; Gilang Maulana Jamaludin; Nuruddin Araniri (South Sulawesi Education Development (SSED), 2024)
Everyone should memorize the Qur'an as it provides guidance for prosperity both here on earth and in the afterlife. The ILHAM technique—a useful technique for remembering that incorporates many intelligences for best memorization outcomes and can help pupils develop self-control—is employed. Regression analysis, correlation analysis, descriptive and verification techniques, and a quantitative approach are used in this work. In order to get data on the impact of the brainwave approach on students' self-control, questionnaires were used as the data collecting instrument. All 66 pupils in Class XI, a full-day program, make up the population under study. The Slovin formula was utilized in this study's sampling approach, and 57 students made up the sample. The ILHAM technique has a low degree of closeness and a favorable influence on self-control in Class XI students at Madrasah Aliyah Negeri 2 Cirebon, according to the findings of the calculation of variables ILHAM technique with self-control in students